2021
DOI: 10.1002/jpln.202000471
|View full text |Cite
|
Sign up to set email alerts
|

Flint maize root mycorrhization and organic acid exudates under phosphorus deficiency: Trends in breeding lines and doubled haploid lines from landraces

Abstract: Aims: High maize yields in modern well‐managed agroecosystems depend on the use of elite varieties and hybrids. Unfortunately, because of repeated selection at high fertilizer rates, some beneficial traits, such as the interaction with arbuscular mycorrhizal fungi or the release of organic acid anions for phosphate mobilization and for attracting beneficial microorganisms, might be gradually declining in modern elite genotypes. However, old founder lines and landraces possibly carry genetic relicts that origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
3
12
0
Order By: Relevance
“…Moreover, the results obtained may be influenced by the properties of the microorganisms in the consortia such as the biological nitrogen fixation, synthesis of phytohormones (IAA, GA3, and cytokinin), and increased availability of micro- and macronutrients (phosphorus and iron) [ 54 ]. All data reported were consistent with the literature [ 2 , 31 , 53 , 55 , 56 , 57 ], that is, the presence of MC in combination with AMF determined an increase in root development, nutrient uptake, and root and shoot biomass. The novelty here is that the results were obtained using a new technology of functionalization and delivery with biochar and in two “in lab”-designed microbial consortia [ 40 ], which were not tested previously on wheat ( T. durum ) and maize ( Z. mays ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the results obtained may be influenced by the properties of the microorganisms in the consortia such as the biological nitrogen fixation, synthesis of phytohormones (IAA, GA3, and cytokinin), and increased availability of micro- and macronutrients (phosphorus and iron) [ 54 ]. All data reported were consistent with the literature [ 2 , 31 , 53 , 55 , 56 , 57 ], that is, the presence of MC in combination with AMF determined an increase in root development, nutrient uptake, and root and shoot biomass. The novelty here is that the results were obtained using a new technology of functionalization and delivery with biochar and in two “in lab”-designed microbial consortia [ 40 ], which were not tested previously on wheat ( T. durum ) and maize ( Z. mays ).…”
Section: Resultssupporting
confidence: 89%
“…Moreover, the agricultural sector is strongly interested in making the cultivation of commodities such as maize and wheat more sustainable because of their relevance to human and animal nutrition, but this will need important changes in fertilization and energy consumption to avoid the production of pollutants [ 22 , 23 ]. Previous studies have evaluated the field application of mycorrhizae to maize [ 24 ] and wheat [ 25 , 26 , 27 ], obtaining promising results, as their application increased the root absorption of micronutrients from the soil [ 28 , 29 , 30 , 31 ]. Other studies have shown that the application of biofertilizers to wheat cultivation is hampered by the variability in plant responses and environmental conditions [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The weak Root/Shoot and RootDiam correlation and that with several other traits that were different in LP and HP, potentially indicates a trade‐off for acclimation to contrasting P conditions, as the increased contribution of one trait resulted in the decreased contribution of another trait (Table 2). The negative trend for PUE in juvenile flints was corroborated in another soil (Li et al., 2021), but as only young roots were considered here, field trials with the investigated genotypes are required to confirm the importance of juvenile PUE traits for adult plants and for final grain yield and grain PUE. Such experiments should also consider other traits that are important for P efficiency in adult plants, such as the presence of cortical root aerenchyma (Postma & Lynch, 2011) or the association with mycorrhiza (Li et al., 2021).…”
Section: Discussionsupporting
confidence: 58%
“…The negative trend for PUE in juvenile flints was corroborated in another soil (Li et al., 2021), but as only young roots were considered here, field trials with the investigated genotypes are required to confirm the importance of juvenile PUE traits for adult plants and for final grain yield and grain PUE. Such experiments should also consider other traits that are important for P efficiency in adult plants, such as the presence of cortical root aerenchyma (Postma & Lynch, 2011) or the association with mycorrhiza (Li et al., 2021).…”
Section: Discussionsupporting
confidence: 58%
“…However, it is unknown whether the increased citrate and malate accumulation in the roots occurred as a result of the plant's response to TH or whether TH was capable of releasing these acids to mobilize Fe. Mycorrhizal fungi, particularly AMF, have been shown to release significant amounts of organic acids in response to phosphorus deficiency in plants (Andrino et al, 2021 ; Li et al, 2021 ). Further research is required to determine how TH promotes the production of organic acids in plants that aid in the acquisition of Fe.…”
Section: Discussionmentioning
confidence: 99%